Administrators' Perceptions of Oral Health Care and Cancer Screening in Long-Term Care Nursing Facilities. (October 2019) - Maramaldi, Peter; Cadet, Tamara; Burke, Shanna; LeCloux, Mary; White, Erina; Kinnunen, Taru Hannele; Kalenderian, Elsbeth
An estimated 1.7 million adults in the United States more than the age of 65 reside in long-term care nursing facilities (LTCNFs), and only 17% of them receive dental care. More than 83% of LTCNF residents require assistance with oral care. Adequate dental care is a preventative behavior for oral cancer. Adults more than age 65 will account for 60% of oral cancer–related deaths, despite an 80% cure rate for early diagnosis. This study sought to expand knowledge of the perceived benefits, barriers, and ability to perform or provide for oral health care and oral cancer screening as reported by Administrators and Directors of Nursing in LTCNFs. Findings indicate that competing demands for resources make oral health a low priority issue and low knowledge about oral cancer risk among nursing home residents, family members, and staff is a barrier. Potential interventions suggested by participants are discussed.